1985
DOI: 10.1007/bf01422855
|View full text |Cite
|
Sign up to set email alerts
|

A study of the crystallinity index of polypropylene fibres

Abstract: Crystallinity measurements were carried out with the help of X-ray diffraction, differential scanning calorimetry (DSC) and density measurements. The results of this study provide a better understanding of the morphology and complex thermal behaviour of polypropylene fibres. Crystallinity studies show that the crystallinity of PP fibres when measured by X-ray and DSC methods as a function of draw-ratios increases with increasing draw-ratios while the crystallinity of the same samples as derived by density meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The samples were allowed approximately 6 h to seek their level of displacement in the column. From the density the according mass crystallinity index X c was calculated as a percentage using the following equation: , where ρ represents the measured density of the tape, ρ c = 938 kg/m 3 is the density of 100% crystallinity, and ρ a = 854 kg/m 3 is the density of amorphous isotactic polypropylene…”
Section: Methodsmentioning
confidence: 99%
“…The samples were allowed approximately 6 h to seek their level of displacement in the column. From the density the according mass crystallinity index X c was calculated as a percentage using the following equation: , where ρ represents the measured density of the tape, ρ c = 938 kg/m 3 is the density of 100% crystallinity, and ρ a = 854 kg/m 3 is the density of amorphous isotactic polypropylene…”
Section: Methodsmentioning
confidence: 99%
“…The increase of the invariant may be explained by the formation of micropores in the fibres. Micropores in drawn polypropylene fibres which did not contain foreign particles were observed by Nurul Huda & co-workers (Nurul Huda, Bauer, Dragaun & Skalicky, 1984;Nurul Huda, Dragaun, Bauer, Muschlik & Skalicky, 1985). The probability of micropore formation is higher when fibres are drawn in the presence of pigments.…”
Section: Invariantmentioning
confidence: 78%
“…And the integrated area also decreased with increasing the organoclay content, which indicated that the crystallinity of nanocomposite fibers was improved. The specific crystallinity of the pure PP and nanocomposite fibers was calculated based on the following formula,34 where I c and I a are the integrated areas of the crystalline and amorphous domains, respectively, and X c is the average crystallinity of the system. The data shown in Table II shows that the crystallinity of the drawn fibers increases with increasing the organoclay content and is higher than that of the pure PP fiber, which suggests again that certain organoclay added to the PP fibers could act as the nucleating agent and promote the crystal growth of the PP crystal in an essential way and perfected the α‐crystalline form.…”
Section: Resultsmentioning
confidence: 99%